2007
DOI: 10.1021/ic700415w
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Ag/1,2,4-Triazole/Polyoxometalates Hybrid Family Varying from Diverse Supramolecular Assemblies to 3-D Rod-Packing Framework

Abstract: Eight members of the Ag/1,2,4-triazole/polyoxometalates (POMs) hybrid supramolecular family, namely, [Ag4(dmtrz)4][Mo8O26] (dmtrz=3,5-dimethyl-1,2,4-triazole, 1), [Ag6(3atrz)6][PMo12O40]2.H2O (3atrz=3-amino-1,2,4-triazole, 2), [Ag2(3atrz)2]2[HPMoVI10MoV2O40] (3), [Ag2(dmtrz)2]2[HPMoVI10MoV2O40] (4), [Ag2(trz)2]2[Mo8O26] (trz=1,2,4-triazole, 5), [Ag2(3atrz)2][Ag2(3atrz)2(Mo8O26)] (6), [Ag4(4atrz)2Cl][Ag(Mo8O26)] (4atrz=4-amino-1,2,4-triazole, 7), and [Ag5(trz)4]2[Ag2(Mo8O26)].4H2O (8), were synthesized through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
97
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 275 publications
(104 citation statements)
references
References 100 publications
7
97
0
Order By: Relevance
“…To the best of our knowledge, these neutral N-containing organic ligands used in the POM-based compounds are usually based on rigid organic ligands, such as bipyridine and triazole [17][18][19][20][21], or flexible organic ligands, such as bis(imidazole) and bis(triazole) [22][23][24][25]. However, examples that employ semi-rigid neutral organic amine ligands [26,27] to construct POM-templated compounds have not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, these neutral N-containing organic ligands used in the POM-based compounds are usually based on rigid organic ligands, such as bipyridine and triazole [17][18][19][20][21], or flexible organic ligands, such as bis(imidazole) and bis(triazole) [22][23][24][25]. However, examples that employ semi-rigid neutral organic amine ligands [26,27] to construct POM-templated compounds have not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that electron-donating thiol group introduced to the N-containing heterocyclic triazole can allow the stabilization of the metal ions in low oxidation states such as Cu(I) and Ag(I) [10]. It is also well known that IB (Cu(I) and Ag(I)) coordination polymers are good candidates for potential semiconductor materials with interesting photophysical and photochemical properties [11,12]. In order to construct new semiconductor materials, in this study we choose AgCl and H 2 trzS as the starting materials and successfully obtained a new Ag(I) compound, [Ag 2 (H 2 trzS) 2 Cl 2 ] n (1), which features a 2D layer framework with a rare inorganic graphite-like [AgS] n layer [13,14].…”
mentioning
confidence: 99%
“…Several groups have introduced mixed ligands into the octamolybdates system. For example, Lu's group prepared an interpenetrated arrangement of two kinds of multi-zig zag chain polymers [Cu(4,4 0 -bipy)(nic)(H 2 O)] 2 [22], and so on. In fact, we focus on the modification of octamolybdates [23], and accordingly we attempt to carry out obtaining new organic-inorganic hybrid octamolybdates compounds with novel structures and interested properties by exploring the rational reaction condition, and then further investigate their potential applications in material science.…”
mentioning
confidence: 99%